Toxic-free inorganic coating materials for flame retardation and prevention of flame spreading on underground infrastructure - Goh, Jin Hong (2018)
Chemically bonded phosphate ceramic (CBPC) is an inorganic solid that has intermediate properties between cement and conventional ceramics. As CBPCs are produced by solution processing at low temperature, this type of ceramics can be utilized as functional coating. Low temperature setting aluminium based phosphate ceramics were produced by two different methods. One involved direct mixing of α-alumina powder with phosphoric acid while the other involved formation of AlH3(PO4)3•3H2O gel phase before mixing with α-alumina. Both methods required heat treatment between 155-175°C for at least 24hrs in order to facilitate the reaction. X-ray diffraction studies showed that the major evolved phosphate peaks in all samples belonged to a water soluble phase Al(H2PO4). The second method yielded insoluble berlinite (AlPO4) phase while AlPO4 only appeared in samples produced by first method after heating at 400°C. DSC from 40-400°C showed that phosphates produced by the second method (separate reaction) were more thermally stable compared to direct reaction method. Furthermore, an endothermic peak was observed in DSC of most samples at 240°C. It was suggested to be the decomposition of Al(H2PO4) into AlPO4 through the XRD analysis of samples that went through a simulated DSC heating process. By analysing the amount of heat absorbed during the endothermic reaction, it was also suggested to be the loss of crystal water within the structure. Overall the separate reaction method is concluded to be better and more practical as the reaction kinetic can be better controlled to produce berlinite and the product has better thermal stability.